2017
DOI: 10.3390/ijerph14050511
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Research-Grade Actigraphy Unit for Measuring Exercise Intensity

Abstract: This study was conducted in a free-living setting to investigate the measurement validity of a research-based actigraph for strolling and jogging, and to provide a reference for actual practice and research. Because inadequate physical activity (PA) or sedentary lifestyle has become the fourth leading risk factor for mortality worldwide, many countries have been vigorously promoting the concept of “active living”, and the public has been investing greater effort into intensifying their PA. Although research-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Similarly, in the present study, we found that <90 min a week of PA reduced HS risk by roughly 25% ( Table 2 ). Although detailed information regarding types and intensities of PA was not included in the KCIS data, previous surveys have shown that about half of Taiwan's residents engage in strolling and brisk walking ( 18 , 19 ). Lower PA times may be perceived as easier goals both to set and to achieve, given that lack of time has been found to be an important barrier to individuals engaging in PA ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the present study, we found that <90 min a week of PA reduced HS risk by roughly 25% ( Table 2 ). Although detailed information regarding types and intensities of PA was not included in the KCIS data, previous surveys have shown that about half of Taiwan's residents engage in strolling and brisk walking ( 18 , 19 ). Lower PA times may be perceived as easier goals both to set and to achieve, given that lack of time has been found to be an important barrier to individuals engaging in PA ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The device was worn on each participant’s dominant hand to measure his or her arm activity in a high proportional integral mode [ 42 ]. Generally, actigraphy features excellent validity and reliability [ 43 , 44 , 45 , 46 , 47 ]. Limb activity and energy expenditure: This study employed the IDEEA 3 (MiniSun LLC, Fresno, CA, USA) to measure the participants’ limb activity and energy expenditure.…”
Section: Methodsmentioning
confidence: 99%
“…In general, there is reasonable intra-class correlation for wearable devices, 49 though there are limitations that have been highlighted in a number of recent studies. For example, one study noted that readings did not correlate with intensity of exercise, 50 and another noted that recorded steps for some wearables fell to zero for speeds of 0.3–0.5 m/s. 51…”
Section: Current Challenges and Opportunitiesmentioning
confidence: 99%